Zebrafish Shoaling, Its Behavioral and Neurobiological Mechanisms, and Its Alteration by Embryonic Alcohol Exposure: A Review - Facciol, Amanda; Gerlai, Robert (Frontiers in Behavioral Neuroscience, 2020)
Social cognition and social behaviours are complex phenomena that involve numerous brain areas and underlying neurobiological mechanisms. Embryonic alcohol exposure may lead to the development of Fetal Alcohol Spectrum Disorder (FASD), a disorder that manifests with varying symptoms including abnormal social behaviour and other cognitive deficits. Animal models have been utilized to mimic aspects of the disease and to study potential underlying mechanisms. The zebrafish is a relative newcomer in this field, but has been suggested as an optimal compromise between system complexity and practical simplicity for modeling FASD. Importantly, due to external fertilization and development of the embryo outside the mother and subsequent lack of parental care, this species allows precise control of the timing and dose of alcohol delivery during embryonic development. Furthermore, the zebrafish is a highly social species and thus may be particularly appropriate for the analysis of embryonic alcohol induced alterations in this context. Here, we provide a succinct review focusing on shoaling, a prominent form of social behaviour, in zebrafish. We summarize what is known about its behavioral mechanisms and underlying neurobiological processes, and how it is altered by exposure to ethanol during embryonic development. Lastly, we briefly consider possible future directions of research that would help us better understand the relationship between the behavioural expression and molecular basis of embryonic ethanol-induced social deficits in fish and humans.